Counseling Relationship for Adherence to Taking Antihypertensive Drugs against Drug Adherence at Sekar Gembong Clinic, Pati, Indonesia - Annis Rahmawaty; Yulia Pratiwi; Rifda Naula Lina; Hasty Martha Wijaya; Dian Arsanti Palupi; Rakhmi Hidayati (Community Medicine and Education Journal, 2023)
Hypertension is a modifiable cardiovascular risk factor for which effective drugs are available to manage elevated blood pressure and prevent complications. Poor adherence will be a source of psychological and medical complications and have an impact on the quality of life of patients, waste health care resources, and reduce individual trust in the health care system. This study aimed to determine the relationship between medication adherence counseling efforts and adherence to hypertension medication taking at Sekar Gembong clinic, Pati, Indonesia. This study is an experimental study, where as many as 50 research subjects participated in this study. Adherence assessment of drugs was carried out with MMAS-8. Data analysis was carried out using SPSS univariate and bivariate. Providing medication adherence counseling improved the level of adherence of research subjects to taking antihypertensive medication, where there was a decrease in the MMAS-8 score after counseling was given compared to before counseling was given, p<0.05. In conclusion, there is a relationship between giving medication adherence counseling and adherence to antihypertensive drugs at Sekar Gembong clinic, Pati, Indonesia.